Criminal identities consumer culture crime, exclusion and the new culture of narcissm - Hall, Steve 1955- (Routledge, 2012)
Offering the first in-depth investigation into the relationship between today's crinimal identities and consumer culture, this book uses unique data - taken from criminals locked in areas of permanent recession - to uncover feelings and attitudes towards a variety of criminal activities.
First published by Willan Publishing 2008
Keywords: Electronic books